2018
DOI: 10.1371/journal.pone.0196745
|View full text |Cite
|
Sign up to set email alerts
|

Mineral licks as environmental reservoirs of chronic wasting disease prions

Abstract: Chronic wasting disease (CWD) is a fatal neurodegenerative disease of deer, elk, moose, and reindeer (cervids) caused by misfolded prion proteins. The disease has been reported across North America and recently discovered in northern Europe. Transmission of CWD in wild cervid populations can occur through environmental routes, but limited ability to detect prions in environmental samples has prevented the identification of potential transmission “hot spots”. We establish widespread CWD prion contamination of m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
53
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(62 citation statements)
references
References 54 publications
0
53
0
Order By: Relevance
“…in Wyoming) increase the risk of disease transmission (Creech et al, 2012). Similarly, recent detection of CWD PrP Sc in ecologically relevant environments, such as natural mineral licks where wildlife obtain minerals from soil and water consumption, suggests a key role of landscape features in CWD transmission risk (Plummer et al, 2018). Thus, identifying where and when CWD occurs in a timely fashion can help inform policies regarding baiting and supplemental feeding of cervids and to consider direct habitat modification with the aim of reducing infectious contact (Sorensen, van Beest & Brook, 2014).…”
Section: Role Of the Environment And Wildlife In The Spread Of Cwdmentioning
confidence: 99%
See 1 more Smart Citation
“…in Wyoming) increase the risk of disease transmission (Creech et al, 2012). Similarly, recent detection of CWD PrP Sc in ecologically relevant environments, such as natural mineral licks where wildlife obtain minerals from soil and water consumption, suggests a key role of landscape features in CWD transmission risk (Plummer et al, 2018). Thus, identifying where and when CWD occurs in a timely fashion can help inform policies regarding baiting and supplemental feeding of cervids and to consider direct habitat modification with the aim of reducing infectious contact (Sorensen, van Beest & Brook, 2014).…”
Section: Role Of the Environment And Wildlife In The Spread Of Cwdmentioning
confidence: 99%
“…For example, focal and consistent culling has been shown to reduce the prevalence of CWD in some wild cervid populations (Manjerovic et al, 2014;Sorensen et al, 2014), and simulations suggest that this approach can even eliminate the disease in certain situations (Potapov, Merrill & Lewis, 2012). This observation suggests that if CWD is discovered in high-value (endangered or conservation priority) isolated populations, where culling is not feasible, field testing and immediate culling of CWD-positive individuals could be economically and logistically feasible (Wolfe, Miller & Williams, 2004;Plummer et al, 2018). Combining theoretical approaches with surveillance data shows that deer density has varying levels of influence on contact rates and mechanisms of transmission (Storm et al, 2013;Potapov et al, 2013;Jennelle et al, 2014).…”
Section: Strategies To Control the Spread Of Cwdmentioning
confidence: 99%
“…saliva) from another infected animal, or contact with body fluids, such as urine or faeces (NYSDEC, 2018). Artificial aggregation of deer: rearing animals in captivity, using urine lures for hunting purposes, feeding during the winter season and placing mineral salt licks in the field even if they are intended for the domestic species Sorensen et al, 2014;Plummer et al, 2018) NYSDEC (2018)…”
Section: Nysdec (2018) Review Fmentioning
confidence: 99%
“…This study shows that although recovery of PrP CWD bound to soil minerals and whole soils with time become more difficult, prion infectivity is not significantly altered. Detection of prions in soil is, therefore, not only affected by soil type but also by length of time of the prion-soil interaction.Pathogens 2020, 9, 311 2 of 9 soils [12]. A number of laboratory studies have, however, suggested a time-dependent decline in the ability to detect rodent prions when bound to soils [22,25].…”
mentioning
confidence: 99%
“…Pathogens 2020, 9, 311 2 of 9 soils [12]. A number of laboratory studies have, however, suggested a time-dependent decline in the ability to detect rodent prions when bound to soils [22,25].…”
mentioning
confidence: 99%